반송층군의 층서, 퇴적시기, 분지 진화에 관한 고찰 - 최영기; 박승익; 최태진 (자원환경지질, 2023)
The Mesozoic Bansong Group, distributed along the NE-SW thrust fault zone of the Okcheon Fold Belt in the Danyang-Yeongwol-Jeongseon areas, contains important information on the two Mosozoic orogenic cycles in the Koran Peninsula, the Permian-Triassic Songrim Orogeny and the Jurassic Daebo Orogeny. This study aims to review previous studies on the stratigraphy, depositional period, and basin evolution of the Bansong Group and to suggest future research directions. The perspective on the implication of the Bansong Group in the context of the tectonic evolution of the Korean Peninsula is largely divided into two points of view. The traditional view assumes that it was deposited as a product of the post-collisional Songrim Orogeny and then subsequently deformed by the Daebo Orogeny. This interpretation is based on the stratigraphic, paleontologic, and structural geologic research carried out in the Danyang Coalfield area. On the other hand, recent research regards the Bansong Group as a product of syn-orogenic sedimentation during the Daebo Orogeny. This alternative view is based on the zircon U-Pb ages of pyroclastic rocks distributed in the Yeongwol area and their structural position. However, both models cannot comprehensively explain the paleontological and geochronological data derived from Bansong Group sediments. This suggests the need for a new basin evolution model integrated from multidisciplinary data obtained through sedimentology, structural geology, geochronology, petrology, and geochemistry studies. 단양-영월-정선지역 옥천습곡단층대에서 북동-남서 방향의 충상단층대를 따라 분포하는 중생대 반송층군은 페름기-트라이아스기 송림조산운동 혹은 쥐라기 대보조산운동의 기록을 간직하고 있기 때문에 한반도 중생대 조산윤회와 지구조진화를 설명하는 데 있어 매우 중요하다. 본 논평에서는 반송층군의 층서, 퇴적시기, 그리고 분지발달사에 관한 그간 연구를 종합하고 향후 연구방향을 제시하고자 한다. 한반도 남부의 중생대 지구조진화 과정에서 반송층군이 가지는 의미에 대한 시각은 크게 두 가지로 나뉜다. 전통적인 견해는 송림조산운동 후기 혹은 종료 후에 (횡)인장 분지에 반송층군이 퇴적된 후 대보조산운동에 의해 변형이 발생한 것으로 간주한다. 이러한 해석은 단양탄전지역을 중심으로 획득한 층서 및 고생물자료와 구조지질연구 결과에 근거한다. 반면 근래 연구 결과로서 반송층군을 대보조산운동과 관련된 조산동시성 퇴적작용의 산물로 보는 해석이 존재한다. 이러한 대안적 시각은 영월지역 일대에 분포하는 화산쇄설암에 대한 U-Pb 절대연령과 해당 지역의 구조지질학적 해석 결과를 바탕으로 한다. 하지만 두 모델 모두 반송층군으로 분류된 퇴적층에서 도출된 고생물자료와 절대연령자료를 종합적으로 설명하지 못한다. 이는 퇴적학, 구조지질학, 지질연대학, 암석학, 지화학 연구를 통해 획득한 다학제적 자료를 종합한 새로운 분지 진화 모델이 필요하다는 점을 시사한다.